The effectiveness of practical work done by pre service teachers - Mkalipi, Thabo (My University, 2017)
The study investigated the effectiveness of practical work done by pre-service teachers in preparing to be science teachers. For this paper the phrase ‘pre-service teachers’ is replaced with the phrase ‘science student teachers’ sometimes used interchangeably. The study was guided by the following research questions: • What type of practical work do science preservice teachers do? • How do science student teachers relate practical work to the concepts being taught in lectures? • To what extent do the practical tasks enable the science student teachers to do/ learn the things the lecturer intended them to do/learn? • To what extent do the practical tasks done by science student teachers align with practical work specified in the CAPS document? This is a case study employing both qualitative and quantitative research. The researcher interviewed participants in order to obtain qualitative data. He used a questionnaire to obtain quantitative data. The type of sampling employed in this study is called comprehensive sampling because the participants were chosen based on a set of criteria. This study uses the constructivism theory as a conceptual framework. The study provided evidence that the type of practical work done by science student teachers is limited to rediscovering what is already known. It was shown that the other types of practical work (investigate phenomena, solve problems etc.) were not entirely covered by science student teachers. The study provided evidence that practical work done by science student teachers is related to the content taught in lecturers. It shows that practicals done at the university relates to what CAPS advocates; however not all the aspects that the CAPS document advocates are covered by science student teachers during practical tasks. The study recommends that practical work done by science student teachers should be designed to cater for specific aims. Also, institutions should provide more resources and support for science student teachers. Key words: Pre-service teachers, inquiry based practical work, nature of scientific inquiry.
Research report submitted in partial fulfilment of the requirements for the degree of Masters of Science in Science Education in the Faculty of Science
Keywords: Teachers-Training of; Creative thinking